The Differential Long-Term Effects of Client-Centered, Developmental Counselling with Individuals and Group - Wearne, T. D. (Canadian Journal of Counselling and Psychotherapy, 2012)
A study involving 541 female students, in four grade levels in an urban commercial secondary school is reported. Each girl was given Super's Work Values Inventory (WVI) for the purpose of identifying what developmental sequence their scores might reveal. Rank order analysis was used to identify changes. No substantial developmental effects were uncovered, although suchslight effects as did occur supported the assumption of a maturation trend. Of particular interest among these data, however, was the degree to which the Grade X group stood apart from the other three grades. Part of this grade X group had been participants a year earlier in a counselling program. Of these 157 girls in grade X, 31 (down from 36) had experienced client-centered developmental individual counselling and 36 had experienced client-centered developmental counselling in groups of six. In both cases the sessions had 15 weeks duration. When the WVI scores for these 67 girls were removed, the remaining grade X's scores fitted the overall maturation patterns expected. Not only were the counselled girls distinctly different from their age peers, but also the recipients of each counselling modality were distinctly different from each other in rank order of their average profile raw scores. These differences seemed to be more related to the nature of the counselling sessions than to maturation. It was concluded that individual and group counselling have distinctively different effects, and that these effects tend to last for extended periods (at least one year) without reinforcement. These findings emerged from the results of atypical statistical procedures developed by one of the authors and are clearly contradictory to the common finding that no differential effects among modalities exist, and that effects tend to extinguish with time. Implications for counselling practice and future research are drawn.